Influence of Using Geosynthetic Clay Liners on Seepage Characteristics Through an Earth Dam - Ameen, Afnan Salah; Irzooki, Raad Hoobi (Salehan Institute of Higher Education, 2026)
In this study, a permeability tank and SEEP/W software were used to examine the effect of geosynthetic clay liners (GCL) on seepage discharge and the phreatic line in earth dams. Initially, the SEEP/W software was validated by comparing its results with experimental results, and the agreement was excellent. Then, various scenarios were numerically completed and studied. The results indicated that adding GCL as a full length on the upstream side of the dam reduced discharge by 99.97% as compared to a dam without GCL. The results also revealed that decreasing the uncovered GCL height, dam height, and upstream head reduced discharge and lowered the phreatic line. Conversely, a decrease in the GCL slope has the opposite effect. Additionally, reducing the dam permeability decreased discharge, but the location of the phreatic line remained constant. By decreasing the dam slope, seepage discharge increases while the observable phreatic line decreases. An empirical equation was developed to determine seepage discharge through the earth dam with only a GCL with a coefficient of determination (R² = 96.4%). Finally, the results show that using an earth dam with a GCL (y = 6 cm) and a medium drain length (Ld = 40 cm) is an effective case to lower the seepage line, reduce seepage discharge, and prevent piping failure.